An Investigation of Residents’ Perceptions of Positive Festival Impacts, Community Attachment and Well-being: A Study on the Jameson Festival, Victoria Falls, Zimbabwe - Banga, Cathrine (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
The aim of this study is to investigate perceived festival impacts and their relationships to community attachment and well-being from residents’ point of view. Through the integration of the Social Exchange (SET) and affect Theories, a conceptual model to test the relationships is developed. The above mentioned relationships are tested through information gathered from residents who have attended the Jameson Festival in Victoria Falls, Zimbabwe. Victoria Falls town is the host community of the event hence a convenience sampling method was used to collect data on the relationships. Data is analyzed via SPSS 21. Results show that festivals foster social community cohesion and community attachment which increase residents’ well-being. Specifically, results indicate that positive perceived impacts (benefit:-community cohesion) led to community attachment and residents’ well-being. Community attachment acts as a mediator between festival impacts (e.g., community cohesiveness) and residents’ well-being. However, the relationship between festivals impact in the form of cultural preservation was not significant. In line with the SET and Affect theories, findings reveal that community attachment is a mediator between positive festival impacts and residents’ well-being. That is, when residents perceive positive festival impacts they become more attached to their community which in turn enhances their well-being. The theoretical implications of the study lie mainly on the introduction of a new theory to the festival body of studies and the study’ findings shed light and direction on practical implications and future directions for festival organizers and scholars.

ÖZ: Bu çalışmanın amacı, algılanan festivalin etkilerini ve bölge sakinlerinin bakış açılarından topluluk bağı ile refah arasındaki ilişkiyi araştırmaktır. Buna ek olarak, entegrasyon yoluyla sosyal değişim ve etki teorisi (SET) ilişkileri test etmek üzere çalışmada kullanılmış ve kavramsal bir model geliştirilmiştir. Yukarıda bahsedilen ilişkiler, Zimbabwe'deki Victoria Şelaleleri'ndeki Jameson festivaline katılan bölge sakinlerine uygulanmıştır. Victoria Şelalesi kasabası, etkinliğin ev sahibi topluluğu olup, ilişkilerle ilgili verileri toplamak için kolaylıklı örnekleme yöntemi kullanılmıştır. Veriler SPSS 21 yazılım programı ile analiz edilmiştir. Sonuçlar, festivallerin, bölge sakinlerinin refahını artıran toplumsal birliktelik ve topluluk bağını teşvik ettiğini göstermektedir. Sonuçlar, özellikle olumlu algılanan etkilerin (yarar: topluluk uyumu) topluluk bağına ve sakinlerin öznel olarak iyi olmalarına yol açtığını göstermektedir. Topluluk bağları, festivalin etkileri (ör., Topluluğun kaynaşması) ve bölge sakinlerinin refahı arasındaki arabuluculuk görevini görmektedir. Öte yandan, bulgular, festivaller arasındaki ilişkinin kültürel koruma biçimi açısından anlamlı olmadığını g,stermekted. Buna ek olarak, sosyal değişim ve etki teorisi bulgularına göre, topluluk bağlarının festivalin etkileri ile bölge sakinlerinin refahı arasında arabulucu olduğunu ortaya çıkarmaktadır. Buna paralel olarak, bölge sakinlerinin festival etkilerinin olumlu olduğunu gördüklerinde topluluklarına daha fazla bağlılık gösterdiklerini ve bunun sonucunda da refahlarının arttığı ortaya çıkmaktadır. Çalışmanın teorik sonuçları, ağırlıklı olarak, festivallerle ilgili literatüre yeni bir teori kazandırmaya dayanmaktadır. Araştırmanın bulguları, festival organizatörlerine ve akademisyenlerine pratik sonuçlar sağlamakta ve gelecekteki yönergeler konusunda ışık tutmaktadır.
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2017. Co-Supervisor: Dr. Georgiana Karadaş and Supervisor: Prof. Dr. Hasan Kılıç.
Keywords: Tourism; Festivals--Tourism; Jameson Festival--Zimbabwe; Community cohesion; community attachment; residents’ well-being; festival; Victoria Falls; Zimbabwe; Affect theory; Exchange theory